Fe-GL-coated Fe < 0 > catalyst and preparation method and application thereof

By preparing Fe-GL@Fe0 catalyst, the problem of difficulty in efficiently removing perfluorinated compounds from water in the existing technology was solved, and efficient removal of perfluorinated compounds was achieved without external energy input, reducing treatment costs and avoiding secondary pollution.

CN120618513AInactive Publication Date: 2025-09-12GUANGZHOU UNIVERSITY

Patent Information

Application Number
CN202511150418.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-09-12
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing technologies make it difficult to remove perfluorinated compounds from water efficiently and economically, and conventional methods require the addition of external oxidants or reducing agents and external energy, which leads to high costs and the risk of secondary pollution.

Method used

A Fe-GL@Fe0 catalyst was developed and prepared by a simple room temperature stirring and calcination method. The catalyst is composed of graphene-like carbon, zero-valent iron, Fe3O4 and Fe3C, and can effectively remove perfluorinated compounds without external energy input.

Benefits of technology

It achieves efficient removal of perfluorinated compounds in water without external energy input, with removal and defluorination rates both greater than 95%. The catalyst is easy to recycle and reuse, reducing treatment costs and avoiding secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120618513A_ABST
    Figure CN120618513A_ABST
Patent Text Reader

Abstract

The invention discloses a Fe-GL-Fe < 0 > catalyst and a preparation method and application thereof, and belongs to the technical field of water treatment. The preparation method is simple, the requirement for equipment is low, the prepared Fe-GL-Fe < 0 > catalyst can effectively remove perfluorinated compounds such as perfluorooctanoic acid, perfluorooctane sulfonic acid, perfluorononanoic acid and perfluorooctane sulfonic acid in water under the environment atmosphere condition without external energy input, and the removal rate and the defluorination rate are both larger than 95%; the catalyst belongs to a solid catalyst, is convenient to separate from water, is recycled, keeps a high removal effect, and is low in metal ion dissolution rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of water treatment, in particular to a Fe-GL@Fe 0 Catalyst, preparation method and application thereof. Background Art

[0002] Per- and polyfluoroalkyl substances (PFAS) are ubiquitous environmental pollutants with over 12,000 unique known structures, including perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorooctanesulfonic acid (PFOS), and perfluorohexanesulfonic acid (PFHxS). The widespread use of PFAS in various fields has led to their unavoidable presence in surface water, municipal wastewater, and even drinking water. Numerous studies have shown that even trace amounts of PFAS pose serious risks to human health and the environment due to their high toxicity, persistence, and potential for bioaccumulation.

[0003] Current methods for removing PFAS include thermal treatment, electrochemical methods, ultrasonic methods, advanced oxidation methods, and ultraviolet oxidation methods. However, these methods require oxidants or reducing agents, as well as external energy sources such as light, electricity, heat, and ultrasound to mineralize PFAS. Furthermore, the ubiquitous presence of dissolved organic carbon and coexisting anions in water can greatly inhibit the destruction of PFAS. Therefore, developing a cost-effective PFAS mineralization technology remains an urgent scientific challenge.

[0004] Based on this, a Fe-GC@Fe catalyst was proposed for PFAS mineralization without the need for additional auxiliary energy and reagents. 0 Catalyst and preparation method thereof. Summary of the Invention

[0005] The purpose of the present invention is to provide a Fe-GL@Fe 0 A catalyst and a preparation method and application thereof are provided to solve the problems in the background technology.

[0006] To achieve the above object, the present invention provides a Fe-GL@Fe 0 The preparation method of the catalyst comprises the following steps: S1. Dissolve ferric nitrate nonahydrate and trimesic acid in deionized water and stir thoroughly to form a light orange suspension A. S2. Add a carbon source and a nitrogen source to the suspension A, stir thoroughly, and dry to obtain a solid B; S3. The obtained solid B was placed in a porcelain boat and calcined in a tube furnace under nitrogen to obtain a black solid. After grinding, Fe-GL@Fe 0 catalyst.

[0007] Preferably, in S1, the amount of ferric nitrate nonahydrate is 3.6-4.4 g, the amount of trimesic acid is 1.1-1.7 g, the amount of deionized water is 40-80 mL, and the stirring time is 2-4 h.

[0008] Preferably, in S2, the carbon source is 5-8 g and the nitrogen source is 2-5 g.

[0009] Preferably, in S2, the carbon source is one or more of mannitol, glucose, polyethylene glycol, pigeon droppings and silkworm feces, and the nitrogen source is one or more of melamine, L-lysine, dopamine hydrochloride and urea.

[0010] Preferably, in S2, the stirring time is 2 to 4 hours, the drying temperature is 80 to 100° C., and the drying time is 24 to 36 hours.

[0011] Preferably, in S3, the heating rate of the tubular furnace is 5-10°C / min, the temperature is maintained at 700-900°C, and the calcination time is 2-4h.

[0012] The present invention also provides a Fe-GL@Fe 0 catalyst, the Fe-GL@Fe 0 The catalyst was prepared by the above preparation method, Fe-GL@Fe 0 The microstructure of the catalyst is a flaky porous material, Fe-GL@Fe 0 The structural composition of the catalyst is graphene-like carbon, zero-valent iron, Fe3O4 and Fe3C.

[0013] Preferably, Fe-GL@Fe 0 In the catalyst, zero-valent iron is tightly coated by iron-complexed graphene-like carbon, making the catalytic performance more stable and not easily dissolved in water; Fe-GL@Fe 0 The catalyst material has a large specific surface area and numerous voids, which can easily expose more reactive sites, promote interfacial contact with PFAS molecules and electron acceptor O2, enhance the mass transfer process, and achieve rapid degradation of PFAS.

[0014] The present invention also provides the above-mentioned Fe-GL@Fe 0 Application of catalyst, the Fe-GL@Fe 0 The catalyst is used to remove perfluorinated compounds from water.

[0015] Preferably, in the process of removing perfluorinated compounds from water, Fe-GL@Fe 0 The catalyst is dispersed in water containing perfluorinated compounds, and the perfluorinated compounds are degraded by stirring under heating in a water bath.

[0016] Preferably, the perfluorinated compound includes one or more of perfluorononanoic acid, perfluorooctanoic acid, perfluoroheptanoic acid, perfluorohexanoic acid, perfluoropentanoic acid, perfluorobutyric acid, pentafluoropropionic acid, trifluoroacetic acid, perfluorooctane sulfonic acid, perfluoroheptane sulfonic acid, perfluorohexane sulfonic acid, perfluoropentane sulfonic acid, perfluorobutane sulfonic acid, perfluoropropane sulfonic acid, perfluoroethane sulfonic acid, and perfluoromethane sulfonic acid.

[0017] Therefore, the present invention provides a Fe-GL@Fe 0 The catalyst, its preparation method and application have the following beneficial effects: (1) The present invention adopts a two-step synthesis method, firstly, a simple room temperature stirring method is used to obtain a precursor, and then a calcination method is used to synthesize the catalyst. The preparation method is simple and the equipment requirements are low; the Fe-GL@Fe prepared by the present invention is 0 The catalyst can effectively remove perfluorooctanoic acid, perfluorooctane sulfonic acid, perfluorononanoic acid, perfluorohexane sulfonic acid and other perfluorinated compounds in water under ambient atmospheric conditions without external energy input, with removal and defluorination rates both greater than 95%. It is a solid catalyst, easy to separate from water, recycle and reuse while maintaining a high removal effect, and has a low metal ion dissolution rate.

[0018] (2) Fe-GL@Fe prepared by the present invention 0 In the catalyst, iron species are encapsulated in a graphene-like framework, which mainly plays the role of regulating the internal electron distribution of the material; zero-valent iron, as an active center, does not directly react with PFAS, iron is non-consumable and has low dissolution; the material has a large specific surface area and many voids, which are conducive to the interfacial contact between the catalyst and PFAS molecules and dissolved oxygen, enhancing the mass transfer process; the carbon, nitrogen, oxygen and iron elements contained in the catalyst are all environmentally friendly elements, and there is no risk of causing secondary pollution.

[0019] (3) The present invention weakens the C-F bond by constructing a sufficiently strong electric field on the catalyst surface, mediating the activation of dissolved oxygen in water, and achieving defluorination, cracking and mineralization of PFAS under mild conditions. No external oxidants or reducing agents are required, and no external energy assistance is required. It is sufficient to treat PFAS in wastewater with low energy consumption and high efficiency, significantly reducing the cost of PFAS wastewater treatment.

[0020] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the XRD spectrum of the catalyst prepared in Example 1 of the present invention; Figure 2 This is a SEM image of the catalyst prepared in Example 1 of the present invention; Figure 3 This is a TEM image of the catalyst prepared in Example 1 of the present invention; Figure 4 This is a transmission electron microscope elemental scanning image of the catalyst prepared in Example 1 of the present invention; Figure 5 Fe-GL@Fe prepared in Example 1 of the present invention 0 High-magnification transmission electron microscopy image of the catalyst; Figure 6 The Fe-GL@Fe in the application example 1 of the present invention 0 Activity evaluation results of the catalyst for removing PFAS from water without external energy input, where a is the degradation curve of PFNA, PFOA, PFHpA, PFHxA, PFPeA, PFBA, PFPrA, and TFA; b is the defluorination curve of PFNA, PFOA, PFHpA, PFHxA, PFPeA, PFBA, PFPrA, and TFA; c is the degradation curve of PFOS, PFHpS, PFHxS, PFPeS, PFBS, PFPrS, PFEtS, and TFMS; d is the defluorination curve of PFOS, PFHpS, PFHxS, PFPeS, PFBS, PFPrS, PFEtS, and TFMS; Figure 7 The Fe-GL@Fe in the application example 2 of the present invention 0 The results of the evaluation of the recycling activity of the catalyst when it begins to degrade PFOA. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described below with reference to the accompanying drawings and embodiments.

[0023] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0024] Example 1 In this embodiment, a Fe-GL@Fe 0 Catalyst, the specific steps are as follows: S1. Dissolve 3.6 g of ferric nitrate nonahydrate and 1.1 g of trimesic acid in 40 mL of deionized water and stir thoroughly to form a light orange suspension A. S2. Add 5 g of polyethylene glycol as a carbon source and 2 g of melamine as a nitrogen source to suspension A, stir thoroughly for 2 h, and dry in an oven at 100 °C for 24 h to obtain solid B; S3. The obtained solid B was placed in a porcelain boat and heated to 900°C in a tube furnace under nitrogen at a heating rate of 10°C / min. The solid was calcined for 4 h to obtain a black solid. After grinding, Fe-GL@Fe0 catalyst.

[0025] The Fe-GL@Fe prepared in Example 1 0 The catalyst was characterized, such as Figure 1 As shown, compared with the standard card, Fe-GL@Fe 0 The catalyst phase composition includes graphene-like carbon, Fe 0 , Fe3O4 and Fe3C. Figure 2 The scanning electron microscope image shows that it is a porous material. Figure 3 The transmission electron microscopy image shows that the black zero-valent iron particles are evenly dispersed on the graphene-like carbon. Figure 4 Elemental analysis revealed that the catalyst was composed of C, N, O and Fe. Figure 5 This indicates that the catalyst contains Fe 0 , Fe2N, Fe3O4 and graphene-like carbon, indicating that the catalyst iron complexes the graphene-like carbon and wraps the zero-valent iron structure.

[0026] Example 2 The preparation steps of this embodiment are the same as those of embodiment 1, except that glucose is used as the carbon source in an amount of 6 g; and dopamine hydrochloride is used as the nitrogen source in an amount of 4 g.

[0027] Example 3 The preparation steps of this embodiment are the same as those of embodiment 1, except that 8 g of silkworm feces are used as the carbon source, and 5 g of urea is used as the nitrogen source.

[0028] Application Example 1 The Fe-GL@Fe prepared in Example 1 0 The catalyst is used to degrade perfluorinated compounds in water. The specific steps are as follows: 0.06 g of Fe-GL@Fe prepared in Example 1 was added 0 The catalyst was added to 100 mL of 1.2 μmol / L PFAS solution. The water quality was deionized water without any oxidant. The degradation reaction began with continuous stirring in a water bath at 30°C. Samples were taken at different time points to determine the PFAS concentration and fluoride ion concentration.

[0029] The above scheme was used to conduct continuous degradation experiments on perfluorononanoic acid (PFNA), perfluorooctanoic acid (PFOA), perfluoroheptanoic acid (PFHpA), perfluorohexanoic acid (PFHxA), perfluoropentanoic acid (PFPeA), perfluorobutyric acid (PFBA), pentafluoropropionic acid (PFPrA), trifluoroacetic acid (TFA), perfluorooctane sulfonic acid (PFOS), perfluoroheptane sulfonic acid (PFHpS), perfluorohexane sulfonic acid (PFHxS), perfluoropentane sulfonic acid (PFPeS), perfluorobutane sulfonic acid (PFBS), perfluoropropane sulfonic acid (PFPrS), perfluoroethane sulfonic acid (PFEtS), and perfluoromethane sulfonic acid (TFMS) in water. The degradation rate results are shown in the following table. Figure 6 As shown in the figure, at 240 min, the removal rate and defluorination rate were both greater than 95%.

[0030] Application Example 2 The Fe-GL@Fe prepared in Example 1 0 The catalyst is used to degrade PFOA in water. The specific steps are as follows: 1) 0.06 g of Fe-GL@Fe prepared in Example 1 was added 0 The catalyst was added to 100 mL of a 1.2 μmol / L PFOA solution in deionized water without any oxidant added. The degradation reaction began with continuous stirring in a water bath at 30°C. 2) After 240 minutes of reaction, the concentration of generated fluoride ions was detected; 3) After the reaction is completed, the Fe-GL@Fe 0 The catalyst was separated and dried, and the dried Fe-GL@Fe 0 The catalyst was used again in the test of degrading perfluorinated compounds in water, i.e., steps 1) to 3) were repeated.

[0031] The Fe-GL@Fe 0 The catalyst is tested for cycle performance, such as Figure 7 As shown, it can be observed that Fe-GL@Fe 0 After continuous cycle reaction, the catalyst's effect on degrading PFOA did not decrease significantly. In 6 repeated experiments, the defluorination rate reached more than 95%.

[0032] Therefore, the present invention provides a Fe-GL@Fe 0 Catalyst and its preparation method and application, the preparation method is simple, the equipment requirements are low, and the prepared Fe-GL@Fe 0The catalyst can effectively remove perfluorooctanoic acid, perfluorooctane sulfonic acid, perfluorononanoic acid, perfluorohexane sulfonic acid and other perfluoro compounds in water under ambient atmospheric conditions without external energy input, with a removal rate and defluorination rate both greater than 95%; the catalyst prepared by the present invention is a solid catalyst, which is easy to separate from water, recycle and reuse while maintaining a high removal effect, and has a low metal ion dissolution rate.

[0033] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solutions of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A Fe-GL@Fe 0 The method for preparing a catalyst is characterized in that: The following steps are involved: S1. Dissolve ferric nitrate nonahydrate and trimesic acid in deionized water and stir thoroughly to form a light orange suspension A. S2. Add a carbon source and a nitrogen source to the suspension A, stir thoroughly, and dry to obtain a solid B; S3. The obtained solid B was placed in a porcelain boat and calcined in a tube furnace under nitrogen to obtain a black solid. After grinding, Fe-GL@Fe 0 catalyst.

2. A Fe-GL@Fe according to claim 1 0 The method for preparing a catalyst is characterized by: In the S1, the amount of ferric nitrate nonahydrate is 3.6-4.4 g, the amount of trimesic acid is 1.1-1.7 g, the amount of deionized water is 40-80 mL, and the stirring time is 2-4 h.

3. A Fe-GL@Fe according to claim 1 0 The method for preparing a catalyst is characterized by: In the S2, the carbon source is 5-8 g, and the nitrogen source is 2-5 g.

4. A Fe-GL@Fe according to claim 1 0 The method for preparing a catalyst is characterized by: In S2, the carbon source is one or more of mannitol, glucose, polyethylene glycol, pigeon droppings and silkworm feces, and the nitrogen source is one or more of melamine, L-lysine, dopamine hydrochloride and urea.

5. The Fe-GL@Fe according to claim 1 0 The method for preparing a catalyst is characterized by: In S2, the stirring time is 2-4 hours, the drying temperature is 80-100° C., and the drying time is 24-36 hours.

6. The Fe-GL@Fe according to claim 1 0 The method for preparing a catalyst is characterized by: In S3, the heating rate of the tubular furnace is 5-10°C / min, the temperature is maintained at 700-900°C, and the calcination time is 2-4 hours.

7. A Fe-GL@Fe 0 A catalyst characterized by: The Fe-GL@Fe 0 The catalyst is prepared by the preparation method according to any one of claims 1 to 6.

8. The Fe-GL@Fe according to claim 7 0 The application of the catalyst is characterized by: The Fe-GL@Fe 0 The catalyst is used to remove perfluorinated compounds from water.

9. The Fe-GL@Fe according to claim 8 0 The application of the catalyst is characterized by: In the process of removing perfluorinated compounds from water, Fe-GL@Fe 0 The catalyst is dispersed in water containing perfluorinated compounds, and the perfluorinated compounds are degraded by stirring under heating in a water bath.

10. The Fe-GL@Fe according to claim 9 0 The application of the catalyst is characterized by: The perfluorinated compounds include one or more of perfluorononanoic acid, perfluorooctanoic acid, perfluoroheptanoic acid, perfluorohexanoic acid, perfluoropentanoic acid, perfluorobutyric acid, pentafluoropropionic acid, trifluoroacetic acid, perfluorooctane sulfonic acid, perfluoroheptane sulfonic acid, perfluorohexane sulfonic acid, perfluoropentane sulfonic acid, perfluorobutane sulfonic acid, perfluoropropane sulfonic acid, perfluoroethane sulfonic acid, and perfluoromethane sulfonic acid.

Citation Information

Patent Citations

  • Method for in-situ extraction of high-activity monatomic catalyst from MOFs-derived metal oxide and application of high-activity monatomic catalyst

    CN119076036A

  • Electrostatic self-assembly 3D nano flower-shaped Z-type heterojunction photocatalyst and preparation method thereof

    CN120001422A

Cited By

  • Catalyst for realizing efficient mineralization of perfluorinated pollutants by utilizing solar photo-thermal conversion as well as preparation method and application of catalyst

    CN122321965A